2010
DOI: 10.1007/s10461-010-9861-2
|View full text |Cite
|
Sign up to set email alerts
|

Stigma, Health Care Access, and HIV Knowledge Among Men Who Have Sex With Men in Malawi, Namibia, and Botswana

Abstract: Same-sex practices are stigmatized in much of sub-Saharan Africa. Cross-sectional relationships between discrimination, access to and use of health care services, and HIV knowledge among men who have sex with men (MSM) were assessed in Malawi, Namibia, and Botswana. A survey and HIV screening were used to explore these variables and the prevalence of HIV. Overall, 19% of men screened positive for HIV infection. Ninety-three percent knew HIV is transmitted through anal sex with men, however, only 67% had ever r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
247
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 302 publications
(264 citation statements)
references
References 20 publications
13
247
1
Order By: Relevance
“…Once with HIV, the stigma tends to be more present and increases the identity of a "socially devaluated group". The prejudice associated with not being heterosexual still restricts the public visibility of men who have sex with men and keeps them hidden from governmental prevention efforts, either due to fear of discrimination or physical harm due to the disclose of their identities or sexual behavior (12)(13)(14) . Stigma to people living with the HIV/Aids may range among countries and even within each of them.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Once with HIV, the stigma tends to be more present and increases the identity of a "socially devaluated group". The prejudice associated with not being heterosexual still restricts the public visibility of men who have sex with men and keeps them hidden from governmental prevention efforts, either due to fear of discrimination or physical harm due to the disclose of their identities or sexual behavior (12)(13)(14) . Stigma to people living with the HIV/Aids may range among countries and even within each of them.…”
Section: Discussionmentioning
confidence: 99%
“…13 In all cases, this stigma is associated with fewer opportunities for HIV diagnosis, due to social invisibility, lower access to services, and less steady sexual partners. However, there is a greater presence of unmet human needs, risky sexual behaviors, multiples sexual partners, and low rate of use of services (11)(12)(13)(14) . Suffering stigma and prejudice contributes to the increase in rates of new infections by HIV, especially due to new possibilities provided by the Internet.…”
Section: Discussionmentioning
confidence: 99%
“…Further, Ross et al documented a large amount of condomless sexual intercourse among Ugandan MSM that was significantly associated with IH. Synthesis of the evidence has consistently documented that stigma is a major determinant of HIV vulnerability in SSA [3,30,31]. In addition, a history of forced sex and alcohol consumption were found by Aho et al to be significantly associated with condomless anal sex among MSM in Abidjan, Ivory Coast [32].…”
Section: Preliminary Evidence Of Syndemic Conditions and Hiv Vulnerabmentioning
confidence: 98%
“…Similarly, Ross et al employed political-economic analysis to document that more HIV risk-taking behaviors exist among MSM residing in countries with a high Gini coefficient (a widely used measure of inequality] and a less-affirmative political climate than they do among MSM residing in countries with a low Gini coefficient and a strongly affirmative political climate [2]. Baral and colleagues also revealed higher rates of HIV prevalence among MSM in countries that have criminalized same-sex relationships [3].…”
Section: Introductionmentioning
confidence: 99%
“…20 Indeed, stigma among healthcare providers has been found to be a barrier to care for multiple vulnerable populations, including people living with HIV (PLWH), people who inject drugs (PWIDs), and men who have sex with men (MSM). [21][22][23] A study on healthcare providers in Malaysia found that physicians' decisions to defer antiretroviral therapy for HIV patients may be due, in part, to prejudice toward these patients. 24 Transgender people may need to access medical care for general and transition-related healthcare needs, including hormone therapy or gender-affirming surgeries.…”
Section: Discrimination From Healthcare Providers and Transgender Healthmentioning
confidence: 99%